Realizamos agrupaciones libres con objetos del aula en los niños y niñas de cuatro años - Mendoza Lazaro, Giovana Genoveva (2018)
The resolution of problems as a focus of the area of mathematics, guides and gives meaning to mathematics education in the purpose that is pursued to develop citizens who act and think mathematically when solving problems with different contexts. In this sense, the grouping carried out in the session among all the boys and girls, promotes the sense of grouping, so with the sample of several objects found in the classroom they develop concrete, graphic, symbolic and formal actions; to reach the grouping of objects with the same characteristics._x000D_ In this way, the problem-centered approach guides mathematical activity in the classroom. In such a way that it allows the children to situate themselves in the different contexts to create, recreate, analyze, investigate, pose and solve problems, try different paths of resolution, analyze strategies and forms of representation, systematize and communicate new knowledge, among others._x000D_ Finally, from the point of view of Lesh & Zawojewski, the resolution of the problems implies the acquisition of increasing levels of capacity on the part of the students, which provides them with a basis for future learning, for effective participation in society and for conducting activities personal Students need to be able to apply what they have learned to new situations. Student-centered study of problem solving provides a window into their abilities to employ basic thinking and other general cognitive approaches to face challenges in life